Behtareen Hazma; Nizam-e-Hazam Aur Uss Kay Masail - Chopra, Deepak; Translated by Rana, Ijaz Ahmad (Lahore Takhliqat, 2006)
The author provides strategies for balancing mind and body to achieve perfect digestion, an essential aspect of lifelong health and well-being.
Keywords: Digestion -- Medicine, Ayurvedic -- Digestive organs--Diseases--Alternative treatment -- Irritable colon--Alternative treatment -- Perfect digestion : the key to balanced living